Comparative Study on the Fungicidal Activity of Metallic MgO Nanoparticles and Macroscale MgO Against Soilborne Fungal Phytopathogens - Chen, Juanni; Wu, Lintong; Lu, Mei; Lu, Shasha; Li, Ziyan; Ding, Wei (Frontiers in Microbiology, 2020)
Abstract Engineered nanoparticles have provided a basis for innovative agricultural applications, specifically in plant disease management. In this interdisciplinary study, by conducting comparison studies using macroscale magnesium oxide (mMgO), we evaluated the fungicidal activity of MgO nanoparticles (nMgO) against soil-borne Phytophthora nicotianae and Thielaviopsis basicola for the first time under laboratory and greenhouse conditions. In vitro studies revealed that nMgO could inhibit fungal growth and spore germination and impede sporangium development more efficiently than macroscale equivalents. Indispensably, direct contact interactions between nanoparticles and fungal cells or nanoparticle adsorption thereof was found, subsequently provoking cell morphological changes by scanning electron microscopy/energy dispersive spectrometry (SEM/EDS) and transmission electron microscopy (TEM). In addition, the disturbance of zeta potential and accumulation of various modes of oxidative stress in nMgO-exposed fungal cells accounted for the underlying antifungal mechanism. In the greenhouse, approximately 36.58% and 42.35% decreases in tobacco black shank and black root rot disease, respectively, could testify to the efficiency by which 500 μg/mL nMgO suppressed fungal invasion through root irrigation (the final control efficiency reached 50.20% and 62.10%, respectively) when compared to untreated controls or mMgO. This study will extend our understanding of nanoparticles potentially being adopted as an effective strategy for preventing diversified fungal infections in agricultural fields.